Does anti-inflammatory diet mitigate the deleterious effect of bisphenol A on mortality in US adults? Results from NHANES 2003–2016 - Liu, Zhao-Yan; Wang, Chen; Huang, Si-Yu; Lu, Xiao-Ting; Yang, Zhi-Jun; Lan, Qiu-Ye; Huang, Bi-Xia; Chen, Si; Li, Meng-Chu; Zhu, Hui-Lian (Ecotoxicology and environmental safety, 2023)
Accumulating evidence linked bisphenol A (BPA) exposure with several diseases and even premature death. We aimed to evaluate the association between BPA exposure and mortality in US adults from the National Health and Nutrition Examination Survey (NHANES, 2003–2016), and to explore whether an anti-inflammatory diet can mitigate the deleterious effect of BPA on mortality. A cohort study including 8142 adults was conducted. Of these, 4143 (50.2%) were men, with a weighted average age of 55.9 years. Urinary BPA was measured by the on-line solid phase extraction, coupled to high performance liquid chromatography and tandem mass spectrometry. Dietary Inflammatory Index (DII) score was calculated based on 28 available kinds of food parameters in NHANES. Cox proportional hazards regression models were applied to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause, cardiovascular disease (CVD), and cancer mortality. After 75927 person-years of follow-up (median, 9.3 years; maximum, 17.1 years), BPA exposure and DII score were independently associated with all-cause mortality. The fully-adjusted HR (95% CI) in the high versus low levels of BPA was 1.33 (1.05–1.70) for all-cause mortality, and the anti-inflammatory versus pro-inflammatory category of DII was 0.70 (0.56–0.87). There was no significant interaction between BPA and DII (p = 0.200). However, an indication of combined effect was found that, participants in subgroups with low BPA exposure and concurrently with anti-inflammatory category of DII score had 53% significantly lower all-cause mortality. Our findings highlight the importance of another monitoring cycles of BPA exposure, and its long-term adverse effects on health, even though the US government had restricted its use nowadays. Besides, we provided a new perspective against the adverse health effect induced by BPA exposure, that future studies could explore the offset impact of other healthy dietary patterns on the deleterious effect of BPA on health outcomes. [Display omitted] •BPA exposure was independently associated with all-cause mortality in US adults.•It is still necessary to monitor BPA exposure and its adverse effects nowadays.•Adherence to an anti-inflammatory diet may offset the effect of BPA on mortality.